1974
DOI: 10.1139/b74-101
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium wilt of chrysanthemum: anatomical observations on colonization of roots, stem, and leaves

Abstract: The morphology and distribution of Verticillium dahliae Kleb. within the ornamental chrysanthemum (Chrysanthemum morifolium Ramat) was determined at intervals after placement of rooted cuttings into infested potting mix. Most infection sites on the root system occurred on roots that developed after potting. Estimates of the number of infection courts per 100 cm of root ranged from 5.6 to 15.8. Root-cortex cells responded to invasion by producing lignitubers and a dark pigment. Microsclerotia had formed within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Ideally, also fungal components, like root and stem infection, should be included in the criterion value, but we have not quantified these parameters. Despite this simplification of reality, root and stem infection by V. dahliae were reasonably in line with data from Evans and Gleeson (1973), Alexander and Hall (1974), Nicot and Rouse (1987b) and Huisman (1988).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Ideally, also fungal components, like root and stem infection, should be included in the criterion value, but we have not quantified these parameters. Despite this simplification of reality, root and stem infection by V. dahliae were reasonably in line with data from Evans and Gleeson (1973), Alexander and Hall (1974), Nicot and Rouse (1987b) and Huisman (1988).…”
Section: Discussionsupporting
confidence: 86%
“…Each of the Y final parameter sets are considered as one of the optimal solutions of the model. For a detailed description and discussion of the optimization J Derived using data from Alexander and Hall (1974), Pollock and Drysdale (1976) and Perry and Evert (1983), who showed that once the root is penetrated, spread can be very fast, resulting at harvest time in completely colonised plants, and from Nicot and Rouse (1987b), who showed that at an inoculum deusity of 15 microsclerotia g J soil Russet Burbank potatoes mayor may not be completely colonised at harvest time. program, see Klepper and Rouse (1991).…”
Section: Constantsmentioning
confidence: 99%
See 2 more Smart Citations
“…dahliae has attributes that make it of particular interest with regard to its potential to colonize, and hence incapacitate, the creeping root system of C. arvense and the new shoots generated each year. It produces conidia within vessels of infected plants that enable it to develop systemically within below-ground and above-ground organs (Wright 1968;Alexander & Hall 1974). The fungus was extremely common in our survey, being found in C. arvense throughout New Zealand and throughout the growing season; 30% and 51% of sites sampled in spring and summer/autumn, respectively (Tables 3 and 6).…”
Section: Discussionmentioning
confidence: 90%